Burt the Beetle lives here! - Spires, Ashley, 1978- (Spires, Ashley, 1978- Burt the Beetle., 2023)
"All Burt the beetle wants to do is settle down and find the perfect home for himself. Should he build his home out of silk like monarch butterflies? Or make it out of wood fibres and saliva like wasps? Or maybe he could just move into a human home? What does the perfect home for a June beetle look like anyways? And how will Burt know when he's found it? Follow along in this charming and humorous tale as Burt learns all about different insect habitats and homes. And maybe, just maybe finds his just-right home."--